Association between disparities in intergenerational economic mobility and cause-specific mortality among Black and White persons in the United States. (October 2021) - Islami, Farhad; Fedewa, Stacey A.; Thomson, Blake; Nogueira, Leticia; Yabroff, K. Robin; Jemal, Ahmedin
Highlights: In the United States, death rates are higher among non-Hispanic Black (Black) persons than among non-Hispanic White (White) persons. Disparities in economic mobility between White and Black persons with a similar parental income in a recent birth cohort—as a measure of ongoing structural racism—is strongly associated with Black-White mortality gaps in mortality. This association was observed for all-cause mortality and mortality from major causes of death. The association is stronger for potentially preventable conditions, including chronic obstructive pulmonary disease (COPD), injury/violence, and cancers of the lung, liver, cervix, bladder, and esophagus. This study indicates structural racism is strongly associated with Black-White disparities in all-cause mortality and mortality from several causes. Abstract: Background: Evidence about the association between structural racism and mortality in the United States is limited. We examined the association between ongoing structural racism, measured as inequalities in adulthood income between White and Black children with similar parental household income (economic mobility gap) in a recent birth cohort, and Black-White disparities in death rates (mortality gap) overall and for major causes. Methods: Sex-, race/ethnicity-, and county-specific data were used to examine sex-specific associations between economic mobility and mortality gaps for all causes combined, heart diseases, cerebrovascular diseases, chronic obstructive pulmonary disease (COPD), injury/violence, all malignant cancers, and 14 cancer types. Economic mobility data for 1978–1983 birth cohorts and death rates during 2011–2018 were obtained from the Opportunity Atlas and National Center for Health Statistics, respectively. Data from 471 counties were included in analyses of all-cause mortality at ages 30−39 years during 2011–2018 (corresponding to partially overlapping 1978–1983 birth cohorts); and from 1, 572 and 1, 248 counties in analyses of all-cause and cause-specific mortality in all ages combined, respectively. Results: In ages 30−39 years, a one percentile increase in the economic mobility gap was associated with a 6.8 % (95 % confidence interval 1.8 %–11.8 %) increase in the Black-White mortality gap among males and a 13.5 % (8.9 %–18.1 %) increase among females, based on data from 471 counties. In all ages combined, the corresponding percentages based on data from 1, 572 counties were 10.2 % (7.2 %–13.2 %) among males and 14.8 % (11.4 %–18.2 %) among females, equivalent to an increase of 18.4 and 14.0 deaths per 100, 000 in the mortality gap, respectively. Similarly, strong associations between economic mobility gap and mortality gap in all ages were found for major causes of death, notably for potentially preventable conditions, including COPD, injury/violence, and cancers of the lung, liver, and cervix. Conclusions: Economic mobility gap conditional on parental income in a recent birth cohort as a marker of ongoing structural racism is strongly associated with Black-White disparities in all-cause mortality and mortality from several causes.